1997
DOI: 10.1007/s004010050655
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and dynamic density of oligodendroglial cytoplasmic inclusions (GCIs) in multiple system atrophy: a correlation between the density of GCIs and the degree of involvement of striatonigral and olivopontocerebellar systems

Abstract: The distribution and dynamic density of oligodendroglial cytoplasmic inclusions (GCIs) were studied based on 30 cases of multiple system atrophy (MSA), including striatonigral degeneration (SND), olivopontocerebellar atrophy (OPCA) and Shy-Drager syndrome. GCIs were widely spread throughout the central nervous system, including the striatonigral and olivopontocerebellar systems. Inclusion-bearing cells appeared to be oligodendrocytes which usually had larger and lighter nuclei than those of normal-looking olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 17 publications
5
74
1
2
Order By: Relevance
“…[5][6][7] Neuropathologic changes in neurones follow a similar system-bound distribution. These changes include variable degrees of neuronal loss and densities of NCIs and NNIs in the striatum, substantia nigra, locus ceruleus, inferior olives, pontine nuclei, cerebellar Purkinje cells, dorsal motor nucleus of vagus, nucleus vestibularis, intermediolateral cell column of the spinal cord, and Onuf's nucleus.…”
Section: Distribution Of Neuronal Loss and Inclusionsmentioning
confidence: 87%
See 1 more Smart Citation
“…[5][6][7] Neuropathologic changes in neurones follow a similar system-bound distribution. These changes include variable degrees of neuronal loss and densities of NCIs and NNIs in the striatum, substantia nigra, locus ceruleus, inferior olives, pontine nuclei, cerebellar Purkinje cells, dorsal motor nucleus of vagus, nucleus vestibularis, intermediolateral cell column of the spinal cord, and Onuf's nucleus.…”
Section: Distribution Of Neuronal Loss and Inclusionsmentioning
confidence: 87%
“…[8][9][10] Because GCIs and oligodendroglial loss show a marked preponderance over NCIs and neuronal loss, it has been suggested that oligodendroglial pathology, perhaps through programmed cell death (apoptosis), may be the primary lesion of MSA. 6,7,10 Evidence for apoptosis occurring in MSA comes from a number of lines of investigation, including increased immunoreactivity of p53 in the striatum and midbrain of MSA cases. 11 Gene upregulation of p53 is recognized to precede apoptosis.…”
Section: Distribution Of Neuronal Loss and Inclusionsmentioning
confidence: 99%
“…Evidence for such a role was presented when studies a decade ago showed that ␣-synucleincontaining aggregates in multiple system atrophy (MSA) were almost completely restricted to oligodendrocytes, with little detection in astroglial or neuronal cells. 2,73,118,145 Here, gray matter areas are affected predominantly with only a limited number of oligodendrocytes. In the following years, postmortem studies in MSA revealed that myelin-forming oligodendrocytes are functionally compromised, leading to demyelination and oligodendroglial cell death.…”
Section: Impact Of Oligodendroglial and Schwann Cells On Motormentioning
confidence: 99%
“…Results of previous studies suggest that GCI can precede neuronal degeneration [12,26]. In the two individuals we report, neuronal cytoplasmic inclusions were sparse, restricted to the pontine nuclei and inferior olive and not associated with neuronal loss or gliosis.…”
Section: Discussionmentioning
confidence: 60%